2003
DOI: 10.1354/vp.40-4-395
|View full text |Cite
|
Sign up to set email alerts
|

A Morphologic and Immunohistochemical Study of the Bronchus-associated Lymphoid Tissue of Pigs Naturally Infected withMycoplasma hyopneumoniae

Abstract: Abstract. Porcine enzootic pneumonia (PEN), caused by Mycoplasma hyopneumoniae (Mh), has been described in pigs in all geographic areas. The disease is characterized by high morbidity and low mortality rates in intensive swine production systems. A morphologic and immunohistochemical study was done to determine the cellular populations present in lung parenchyma of infected pigs, with special attention to the bronchusassociated lymphoid tissue (BALT). Polyclonal and monoclonal antibodies were used for the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 24 publications
(56 reference statements)
6
68
1
5
Order By: Relevance
“…The cranioventral consolidation observed in the lung samples obtained in this study has also been reported in other studies involving Mycoplasma hyopneumoniae (Sarradel et al 2003, Redondo et al 2009) and can be attributed to the accumulation of mucus and exudates caused by a loss of mucociliary function, increased production of mucus by the globlet cells, bronchoconstriction caused by chemical mediators released by the alveolar macrophages, and the presence of BALT hyperplasia.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The cranioventral consolidation observed in the lung samples obtained in this study has also been reported in other studies involving Mycoplasma hyopneumoniae (Sarradel et al 2003, Redondo et al 2009) and can be attributed to the accumulation of mucus and exudates caused by a loss of mucociliary function, increased production of mucus by the globlet cells, bronchoconstriction caused by chemical mediators released by the alveolar macrophages, and the presence of BALT hyperplasia.…”
Section: Discussionsupporting
confidence: 88%
“…Among the histological ϐindings in the swine lungs, BALT hyperplasia is one of the most indicative of M. hyopneumoniae infection (Sarradel et al 2003, Redondo et al 2009, Hansen et al 2010. The presence of macrophages, neutrophils and alveolar edema is commonly associated with secondary bacterial infection (Redondo et al 2009, Hansen et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A pneumonia enzoótica suína, causada primariamente pelo Mycoplasma hyopneumoniae, é uma doença respiratória crônica distribuída mundialmente, e pode afetar 70 a 100% dos animais em um rebanho de suínos (Kwon et al 2002, Sarradel et al 2003. Essa bactéria coloniza a superfície do epitélio respiratório resultando em diminuição e perda da atividade ciliar e degeneração das células epiteliais (Sarradel et al 2003, Thacker 2004.…”
Section: Introductionunclassified